A review of issues of nomenclature and taxonomy of Hypericum perforatum L. and Kew's Medicinal Plant Names Services. (16th October 2017) - Dauncey, Elizabeth Anne; Irving, Jason Thomas Whitley; Allkin, Robert
Abstract: Objectives: To review which names are used to refer to Hypericum perforatum L. in health regulation and medicinal plant references, and the potential for ambiguity or imprecision. Key findings: Structured searches of Kew's Medicinal Plant Names Services Resource, supplemented with other online bibliographic resources, found that the scientific name Hypericum perforatum L. is used consistently in the literature, but variation between subspecies is rarely considered by researchers. Research is still published using only the common name 'St John's wort' despite it being imprecise; at least 80 other common names are also used for this plant in multiple languages. Summary: Ambiguous and alternative plant names can lead to ineffective regulation, misinterpretation of literature, substitution of raw material or the failure to locate all published research. Kew's Medicinal Plant Names Services (MPNS) maps all names used for each plant in medicinal plant references onto current taxonomy, thereby providing for disambiguation and comprehensive access to the regulations and references that cite that plant, regardless of the name used. MPNS also supplies the controlled vocabulary for plant names now required for compliance with a new standard (Identification of Medicinal Products, IDMP) adopted by medicines regulators worldwide.